An online survey of Turkish psychiatrists’ attitudes about and experiences of adult attention deficit hyperactivity disorder in clinical practice - Altın M; Altın GE; Semerci B (Neuropsychiatric Disease and Treatment, 2016)
Murat Altın,1 Gamze Ergil Altın,2 Bengi Semerci3 1Department of Psychiatry, Medical Park Gaziosmanpasa Hospital, 2Department of Psychiatry, Boylam Psychiatry Institute, 3Department of Psychiatry, Bengi Semerci Institute, Istanbul, Turkey Objective: Although adult attention deficit hyperactivity disorder (ADHD) often persists beyond childhood, daily clinical practices and transition of adult patients with ADHD into adult mental health services in Turkey are not well studied. The aim of this study was to provide data about the presentation of adult patients with ADHD and evaluate the treatment strategies of Turkish adult psychiatrists based on their personal clinical experience in different hospital settings.Methods: A cross-sectional online survey to be filled out by Turkish adult psychiatrists was designed and administered in May 2014. The survey focused on the treatment environment, patterns of patient applications and transition, treatment strategies, and medication management for adults with ADHD.Results: Significant differences were observed in the number of adult patients with ADHD in follow up, and a significant positive correlation was found between number of adult patients with ADHD in follow up and the clinician’s opinion about their level of self-competence to treat adult ADHD. A significant portion of adult psychiatrists have not received any information about their adult ADHD patients’ treatment during childhood. The most preferred medical treatment was stimulants and the majority of the participants always preferred psychoeducation in addition to medication treatment. A majority of participants did not define themselves competent enough to treat and follow up adult patients with ADHD.Conclusion: The findings of this study indicate the need to increase the knowledge, skills, and awareness of adult psychiatrists about adult ADHD. In addition, a more collaborative working relationship between child and adolescent psychiatrists and adult psychiatrists with a definite transition policy is required in order to help patients with ADHD more effectively. Keywords: attention deficit hyperactivity disorders, transition, treatment strategies